1996
DOI: 10.1021/jp952526p
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Dispersion of Nickel Ions in the NiO−MgO System by X-ray Absorption Fine Structure

Abstract: NiO−MgO samples (Ni x Mg1-x O:x = moles of Ni/(moles of Ni + moles of Mg)) were prepared by impregnation of MgO powder with an aqueous solution of Ni(NO3)2, followed by calcination at 773 K. The dispersion of Ni ions in these samples has been studied by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and X-ray absorption fine structure (XAFS). XPS of the depth profile of the samples shows that the atomic concentration of Ni and Mg against the depth is almost constant and close … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 45 publications
9
55
0
Order By: Relevance
“…The energy was defined by assigning the first characteristic peak of the Cu foil spectrum to 8978.9 eV. 26) The spectrum of the Ce/SiO 2 sample of high Ce loading (>1 mol%) was recorded in a transmission mode. For determination of incident x-ray intensity, an ionization chamber (17 cm) filled with N 2 (30%)-He(70%) was used, and for transmission x-ray an ionization chamber (31 cm) filled with N 2 (85%)-Ar(15%) was used.…”
Section: Measurementsmentioning
confidence: 99%
“…The energy was defined by assigning the first characteristic peak of the Cu foil spectrum to 8978.9 eV. 26) The spectrum of the Ce/SiO 2 sample of high Ce loading (>1 mol%) was recorded in a transmission mode. For determination of incident x-ray intensity, an ionization chamber (17 cm) filled with N 2 (30%)-He(70%) was used, and for transmission x-ray an ionization chamber (31 cm) filled with N 2 (85%)-Ar(15%) was used.…”
Section: Measurementsmentioning
confidence: 99%
“…In addition, the k3-weighted CO Kedge EXAFS of the sample of X = 0.02 (Fig. 2.4 was almost identical to the k3-weighted Ni K-edge EXAFS of Ni0.02Mg0.980 solid solution, [3] supporting the formation of Co0.02Mg0.980 solid solution. As shown in Fig.…”
Section: Co K-edge Xafsmentioning
confidence: 52%
“…Previously, we reported that Ni ions form a solid solution with MgO when the samples were prepared by impregnation of MgO powder with an aqueous solution of Ni(NO3h, followed by calcination at 773 K [3]. In the present work, we prepared Coo-MgO samples (CoxMgl-,O : X = m01 of CO / (m01 of CO + m01 of Mg )) with the same method, and investigated the atomic concentration range of CO for formation of a solid solution and the state of CO ions dissolving in the samples mainly by XAFS.…”
Section: Introductionmentioning
confidence: 99%
“…Calcination at 650 ∘ C or higher is beneficial for formation of the solid solution [2,3]. It is also reported that at calcination temperature of 500 ∘ C the solid solution was formed without or with formation of a minor amount of NiO [4,5]. It appears that a uniform dispersion of the two kinds of metallic ions in precursor allows the solid solution formed at a lower calcination temperature [6].…”
Section: Introductionmentioning
confidence: 93%